Skeletal Material from the Gniezno Cathedral (10 Th - 17 Th Centuries). - Kaszycka, Katarzyna (Anthropological Review, 1987)
The Cathedral in Gniezno erected just after the introduction of Christianity in the 10th century A. D. was from the very beginning the place where outstanding personalities (princes, archbishops) were being buried in graves situated in the aisles under the floor. As a result of excavations carried out in the basement of the Cathedral in places indicated in Fig. 1 from 1957 to 1963 and from 1985 to 1987, remains were found of about 100 persons from the / following strata: Pre-Roman (turn of the 10th century),1 Roman (11th - 14th centuries), and Gothic (14th - 17 th centuries) - Figs. 2 - 4. Because of a bad state of preservation of the skeletons only 41 crania and 65 skeletons in which at least one long bone was preserved proved suitable for craniometric and osteological examination (Table 2). Basic ; statistical characteristics of selected metric traits and indices of the crania are presented in Table 3, whereas the statistical characteristics of the traits of long bones and the, reconstructed body height in Table 4. The material from the Gniezno Cathedral is discussed against the background of 15 other skeletal series from Poland dating back to the early and late Mediaeval Ages (Table 5, Fig. 5). In order to determine the degree of mutual similarities and differences between the samples geometric distances C²ıı (Table 6) were calculated for 10 traits of the - crania and 5 traits of long bones. The distances which significantly differed from zero were marked by asterisks.